2020
DOI: 10.1038/s41467-020-19931-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gut microbiota on depressive-like behaviors in mice is mediated by the endocannabinoid system

Abstract: Depression is the leading cause of disability worldwide. Recent observations have revealed an association between mood disorders and alterations of the intestinal microbiota. Here, using unpredictable chronic mild stress (UCMS) as a mouse model of depression, we show that UCMS mice display phenotypic alterations, which could be transferred from UCMS donors to naïve recipient mice by fecal microbiota transplantation. The cellular and behavioral alterations observed in recipient mice were accompanied by a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
169
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(194 citation statements)
references
References 88 publications
19
169
2
4
Order By: Relevance
“…FMT of conventionally raised mice to germ-free mice induced changes in intestinal eCB levels and eCBome gene expression, strengthening the link between gut microbiota and the eCBome [98]. Moreover, FMT from mice with unpredictable mild chronic stress to naïve mice showed a transfer of depressive phenotypes that was concomitant with a decrease in eCBs and peripheral levels of fatty acids [68]. Studies relating to the relationship between diet, gut microbiota, and plasma eCBs showed correlation between several gut microbes and circulating eCBs, which was also influenced by fat mass and fatty acid intake [99,100].…”
Section: Potential Interactions Between Gut Microbiota Inflammation and Endocannabinoidome In Mental Conditionsmentioning
confidence: 79%
See 2 more Smart Citations
“…FMT of conventionally raised mice to germ-free mice induced changes in intestinal eCB levels and eCBome gene expression, strengthening the link between gut microbiota and the eCBome [98]. Moreover, FMT from mice with unpredictable mild chronic stress to naïve mice showed a transfer of depressive phenotypes that was concomitant with a decrease in eCBs and peripheral levels of fatty acids [68]. Studies relating to the relationship between diet, gut microbiota, and plasma eCBs showed correlation between several gut microbes and circulating eCBs, which was also influenced by fat mass and fatty acid intake [99,100].…”
Section: Potential Interactions Between Gut Microbiota Inflammation and Endocannabinoidome In Mental Conditionsmentioning
confidence: 79%
“…To sum up, physical activity and its impact on eCB signaling in animals produce a yet to be fully understood impact on running performance, motivation, memory, and neuroplasticity, through hippocampal CB1 signaling. CB1 could also play a role in those metabolic-driven inflammatory processes and excessive weight gain that extensively impact on neural functions [68].…”
Section: Hippocampal Endocannabinoidomementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Bercik et al (2011) have shown that transferring fecal content from an innately stress-sensitive mouse to non-anxious mice is sufficient to elicit anxiety-like reactions (i.e., reduced exploratory behavior) in the receiver animal. Correspondingly, the reverse pattern, that is, transferring portions of GM from non-anxious mice to innately anxious mice induces the latter to manifest reduced anxiety (for an analogous result, see also the more recent Chevalier et al 2020).…”
Section: The Mgb Axis and Emotional Processingmentioning
confidence: 95%
“…Whether modifications in microbiota composition impact brain function remains elusive although the involvement of immune (proinflammatory cytokines), neural (spinal and vagus nerves), metabolic (short-chain fatty acids), endocrine and neurotransmitter pathways have been suggested 2 . A recent study 8 provided mechanistic evidence suggesting that stress, diet and gut microbiota generate a pathological feedforward loop that contributes to depressive disorders via the central endocannabinoid system. However, such a loop has not been demonstrated for other disorders that can be induced by stress, for instance cognitive alterations.…”
Section: Introductionmentioning
confidence: 99%